Stakeholders' solutions to antiretroviral therapy interruption during the COVID-19 pandemic in China: a short report. Issue 5 (4th May 2023) - Zhan, Yuewei; Sun, Yinghui; Feng, Anping; Li, Hui; Gao, Yanxiao; Liu, Yi; Fitzpatrick, Thomas; Liang, Bowen; Fu, Leiwen; Wang, Bingyi; Wu, Dan; Zhai, Xinyi; et al.
ABSTRACT: Obtaining antiretroviral therapy (ART) was a challenge for people living with HIV (PLHIV) in China during the COVID-19 outbreak. On 26 January 2020, the Chinese Center for AIDS/STD Control and Prevention issued a nationwide directive to relax restrictions on where and when PLHIV could refill ART. This qualitative study explored unexpected barriers under this directive and recommendations to improve future ART delivery. Between February 11 and February 15 2020, in-depth interviews of 4 groups of stake holders related to ART refilling (i.e., PLHIV, community-based organization employees, CDC staff, infectious disease physicians and nurses), were conducted via WeChat. Data were managed by NVivo 11.0 and transcripts were coded using thematic analysis. Sixty-two interviews were conducted. The main barriers to refilling ART included: (1) inconsistent documentation requirements to refill ART, (2) lack of specific protocols on ART refilling, (3) insufficient staffing, and (4) regimen verification and drug shortages. The most common recommendations to improve future ART delivery were: (1) to establish a nationwide system to distribute ART and (2) increase the number of pills delivered with each ART refill. Strengthening protocols and systems to refill ART and improving collaboration is key to preventing interruptions in ART among PLHIV during public health emergencies.